Designing with differences, cross-disciplinary collaboration in transport infrastructure planning and design. (March 2020) - Löfgren, Sofia
Abstract: The study explores enablers and barriers of collaborative planning and design work in transport infrastructure planning projects, drawing upon five cases of projects in Sweden. The study apply a set of theoretical lenses complied of previous research focusing professional knowledge and co-production in planning and design practices, and research revolving around the concept of boundary objects in studies of collaborative work. The study provides insights into the mechanisms of practitioners' learning across professional boundaries: what they learn from each other, how they learn, and how the learning facilitates collaborative work. The results show that disciplinary barriers can be bridged through both individual efforts and project management strategies. This study shed light a set of enablers on individual level including; 1) a capacity to change focus between solving tasks within the remit of one's own discipline and jointly solving tasks together with professionals representing other disciplines; 2) curiosity and interest other professional perspectives; 3) willingness to learn from other professionals; and 4) motivation to engage in cross-disciplinary design processes. Project management is proposed to enable collaboration by; 1) opening up discussions about reasons and motives for collaborative work; 2) opening up discussions about strategies for collaborative processes; 3) promoting and facilitating learning processes among project participants, 4) coordinating meetings and activities for collaboration, and 5) facilitating deliberative dialogues at project meetings in which different types of knowledge can be put forth and interrelated. Highlights: The study identifies enablers and barriers in co-design involving landscape architects and engineers. Learning about differences across disciplinary boundaries is essential for collaborative design. Collaboration is facilitated through activities such as meetings, joint study visits and field trips.